Crystal structure of 2-benzylamino-4-(4-bromophenyl)-6, 7-dihydro-5H-cyclopenta[b]pyridine-3carbonitrile. (March 2015) - Nagalakshmi, R. A.; Suresh, J.; Maharani, S.; Kumar, R. Ranjith; Lakshman, P. L. Nilantha
No abstract available